2019
DOI: 10.1016/j.sopen.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of laparoscopic and open CAPD catheter placement: A single-center experience

Abstract: Background Continuous Ambulatory Peritoneal Dialysis (CAPD) catheter placement is typically a straightforward surgical procedure performed on chronically ill patients with end-stage renal disease (ESRD). Post-operative outcomes and reoperative rates vary greatly in the medical literature. We report our experience using both minimally invasive and open techniques in placing CAPD catheters and offer our surgical outcomes. Methods This study is an IRB-approved, retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In this study, overall, 24.1% of the patients experienced at least one early complication, which is in line with other studies which have reported the rate of such complications to be between 15% and 37.8%. [2][3][4] By contrast, in García-Cruz et al, none of the patients who underwent laparoscopic peritoneal dialysis catheterization suffered from an early complication of peritoneal dialysis catheter insertion. 5 The most frequent early complication of peritoneal dialysis catheter insertion in our study was mechanical complication (16.7%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, overall, 24.1% of the patients experienced at least one early complication, which is in line with other studies which have reported the rate of such complications to be between 15% and 37.8%. [2][3][4] By contrast, in García-Cruz et al, none of the patients who underwent laparoscopic peritoneal dialysis catheterization suffered from an early complication of peritoneal dialysis catheter insertion. 5 The most frequent early complication of peritoneal dialysis catheter insertion in our study was mechanical complication (16.7%).…”
Section: Discussionmentioning
confidence: 97%
“…Displacement and migration of the catheter from the pelvis to other parts of the abdomen is another complication of catheter insertion which was seen in 2.5% of the patients, but it was found to be between 4 and 15% in other studies. 1,4,14 This may be due to the use of a laparoscope to properly insert the catheter in place, in addition to other factors including the use of a low volume of dialysis fluid, the use of heparin after catheter placement, the low-volume changes in the first two weeks after catheterization, and the use of laxatives in patients to avoid constipation regardless of the type of surgical technique.…”
Section: Originalmentioning
confidence: 99%
“…The traditional techniques used for open and laparoscopic insertion of a PD catheter require availability of operating theater time and general anesthesia, which can impede timely catheter insertion and restrict access for patients with significant comorbidities. And laparoscopic catheter placement has been shown to have no superiority to open surgery ( 5 , 6 ). In the present study, we present a modified Seldinger technique for placement of a Tenckhoff PD catheter.…”
Section: Discussionmentioning
confidence: 99%